Reconstruction of Global Moral Values Through Anthony Giddens' Structuration Theory in Responding to Ethical Diversity in the Modern Era - Miftakhur Rohman (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
It is often said that